Knowledge management systems use and competency development among knowledge workers: The role of socio-technical antecedents in developing autonomous motivation to use - Oyefolahan, I.O. (2013)
Purpose: The purpose of this research is to investigate how socio-technical factors inherent in organizational practices and knowledge management systems (KMS) lead to the emergence of autonomous motivation to use KMS and which in turn influences actual utilization and competency development as an impact of KMS utilization. Design/methodology/approach: This research takes a quantitative approach to data collection on the constructs measuring socio-technical factors, autonomous motivation, KMS utilization and competency development. The survey consisted of 306 knowledge workers across different organizations in Malaysia with experience using KMS. The data collected were analysed using structural equation modelling approach with AMOS software. Findings: The research findings indicate that the existence of innovative norms in organizations and KMS that provide adequate linkages or connections among knowledge workers are significantly and positively related with the development of autonomous motivation towards KMS use. In addition, autonomous motivation to use was found to have substantial influence on KMS usage and moderately influences the development of competency. Finally, the actual utilization of KMS was found to be contributing significantly to competency development among knowledge workers. Research limitations/implications: Although the approach of this study is aimed at generalization of results with the combination of responses from individuals working in different organizational settings, few limitations may still affect the scope of the study. First, only an innovative norm is considered as an organizational factor in this research, other constructs such as collaboration and structure are important factors which can be explored in a future study. Secondly, the study is limited to a single country; future studies may include knowledge workers from different countries with exposure to different cultures. Practical implications: The research offers recommendations and suggestions to managers and top management on the organizational practices and KMS design that can make knowledge workers volitionally utilize the KM systems as well as how the impact of implemented KMS on knowledge workers can be measured. Originality/value: The conceptualization of autonomous motivation to use KMS and the factors contributing to it, as well as identification of competency development as a benefit of KMS use, represent an innovation in the theoretical perspective. Â© Emerald Group Publishing Limited.